Epilogue: Cultural History in Retrospect - Salmi Hannu (Routledge, 2022)
The Epilogue discusses current challenges for cultural historial research. It starts with the devastating fire that confronted the medieval cathedral Notre Dame de Paris in 2019 and explores the fragility of the past. It moves forward to the recent theoretical emphasis on nonhuman agency and argues that the study of human/non-human entanglements is essential for understanding human-ness. The present prediction of future changes in climate, economy and global sustainability refers to major challenges during the forthcoming decades. For understanding these changes, it remains vital to look back into the past from new perspectives, not only by focussing on things that have been remembered, but also by trying to find territories that have not yet even been conceived in historical terms.
The Routledge Companion to Cultural History in the Western World